Using Qualitative Methods to Understand the Interconnections Between Cities and Health: A Methodological Review - José Pedro Silva; José Pedro Silva; José Pedro Silva; Ana Isabel Ribeiro; Ana Isabel Ribeiro; Ana Isabel Ribeiro (Frontiers Media S.A., 2024)
Objective: Using different perspectives and methods to investigate the links between the urban phenomenon and health is critical in an urbanizing world. This review discusses qualitative methods in the context of urban health research.Methods: We conducted a narrative review following these steps: We identified the qualitative data collection, analysis and sampling methods that could be more relevant for the problems researched in the urban health field. We conducted searches for methodological articles and other documents about those methods. We included some influential materials and examples of empirical urban health studies using those methods.Results: We included 88 studies and identified several qualitative data gathering, analysis and sampling methods relevant for urban health researchers. We present those methods, focusing their strengths and limitations, and providing examples of their use in the field of urban health. These methods are flexible and allow in-depth analysis of small samples by collecting and analyzing rich and nuanced data.Conclusion: This article should contribute to a better understanding of how, and when, qualitative methods may improve our knowledge on urban health.